Komunikasi dalam Organisasi (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
The purpose of conducting this community service activity is to provide an understanding of communication within a good organization or its benefits to male and female students at the Yauma orphanage located on Paeban Street, Central Jakarta, on Mondays. After the completion of this activity, it is expected that male and female students will have an improved understanding of communication with humans and the connection with the divine, as servants of Allah among the people. This community service activity is held for one day. In the implementation of this community service activity, the problem found is that male and female students still lack an understanding of how to communicate effectively within an organization, following the principles of communication with a smile and greetings in accordance with the guidance of Allah and His Messenger, as stated in Surah An-Nisa: 59. The results of the community service activity show that there has been an increase in understanding among male and female students at the Yauma orphanage regarding effective organizational communication and its benefits. Overall, the community service activity received a positive and enthusiastic response from the Yauma orphanage in Paseban, Central Jakarta.